EVALUATING THE OPERATIONAL EFFICIENCY OF “TOSHSHAHARTRANSXIZMAT” PUBLIC TRANSPORT UNITS: A CASE STUDY FOR THE YEARS 2020–2023 - Komilov , Asror; Kadirov , Tuygun (Techscience uz - Topical Issues of Technical Sciences, 2025)
This study analyzes the operational efficiency of “Toshshahartransxizmat,” a public transport service provider in Tashkent city. Eight bus depots under the enterprise were selected as Decision-Making Units (DMUs), and the analysis was conducted based on data from 2020 to 2023. Using the Panel-Corrected Standard Errors (PCSE) regression method, the most impactful input factors on the output indicators were identified and their statistical significance was assessed. Based on the results, the Data Envelopment Analysis (DEA) model was applied to calculate efficiency scores. This model enables performance improvement for less efficient DMUs by aligning their operations with highly efficient counterparts.